Nonnus of Panopolis in context II : poetry, religion, and society ; proceedings of the international conference on Nonnus of Panopolis, 26th - 29th September 2013, University of Vienna, Austria - Bannert, Herbert.; Kröll, Nicole. (Mnemosyne, Supplements, 2017)
Nonnus of Panopolis in Upper-Egypt is the author of the 48 books of the last large scale mythological epic in antiquity, the Dionysiaca . The same author also wrote an epic poem on the life and times of Jesus Christ according to St John's Gospel . Nonnus has an outstanding position in ancient literature being at the same time a pagan and a Christian author, living in a time when Christianity was common in the Roman empire, while pagan culture and traditional world views were still maintained. The volume is designed to cover literary, cultural and religious aspects of Nonnus' poetry as well as to highlight the social and educational background of both the Dionysiaca and the Paraphrasis of the Gospel of St. John .